A novel adaptive event-triggered reliable $ H_∞ $ control approach for networked control systems with actuator faults - Xingyue Liu; Kaibo Shi; Yiqian Tang; Lin Tang; Youhua Wei; Yingjun Han (Electronic Research Archive, 2023)
In this paper, a reliable $ H_∞ $ control approach under a novel adaptive event-triggering mechanism (AETM) considering actuator faults for networked control systems (NCSs) is addressed. Firstly, the actuator faults are described by a series of independent stochastic variables obeying a certain probability distribution. Secondly, a novel AETM is presented. The triggering threshold can be dynamically adjusted according to the fluctuating trend of the current sampling state, resulting in saving more limited network resources while preserving good control performance. As a result, considering the packet dropout and packet disorder caused by the communication network, the sampling-data model of NCSs with AETM and actuator faults is constructed. Thirdly, by removing the involved auxiliary function and replacing it with a sequence of integrals only related to the system state, a novel integral inequality can be used to reduce conservatism. Thus, a new stability criterion and an event-triggered reliable $ H_∞ $ controller design approach can be obtained. Finally, the simulation results are presented to verify the progressiveness of our proposed approach.